Exploratory Non-Causal Associations of Variables with New-Onset Atrial Fibrillation Incidence and Mortality in Critically Ill Patients [Response To Letter] - Zhang HD; Ding L; Shen YJ; Tang M (Clinical Epidemiology, 2025)
Hong-Da Zhang, Lei Ding, Yu-Jing Shen, Min Tang State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100037, People’s Republic of ChinaCorrespondence: Min Tang, State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, 167 Beilishi Road, Xicheng District, Beijing, 100037, People’s Republic of China, Email doctortangmin@yeah.net